PENGARUH KOMISARIS INDEPENDEN DAN LEVERAGE TERHADAP KUALITAS LABA DENGAN FIRM SIZE SEBAGAI VARIABEL MODERASI - Muslikhatun Muslikhatun; Hidayatul Khusnah (STIE Mahardhika, 2023)
This study looked at how leverage and independent commissions affected the quality of earnings in manufacturing firms in the consumer products sector, with company size acting as a moderating factor. Data from annual financial reports and consolidated financial statements of manufacturing businesses in the consumer products industrial sector listed on the IDX between 2016 and 2020 were used in this study as secondary data. In this study, 21 businesses made up the sample. Purposive sampling is employed in this study, and WarpPLS 7.0 is used to analyze the data. The findings revealed that while leverage had a favorable and minor impact on profits quality, the independent commissioner had a negative and considerable impact. The influence of independent commissioners on the caliber of earnings cannot be moderated by firm size. Firm size is unable to mitigate the impact of debt on the quality of earnings.